(untitled) (Global Journal of Medical Research, 2015)
Background: Risk stratification for aortic dissection (AD) or rupture based on ascending aortic diameter and connective tissue disorders are inadequate. We have evaluated the impact of aortic wall thickness (AWT) on aortic wall quality. Methods: Aortic wall cohesion of 496 patients divided into two groups according to AWT was analyzed using the Dissectometer, a device mimicking transverse shear stress. Correlation of cohesion testing (P7,P8,P9), histology as well as diameter of the ascending aorta with AWT were analyzed. Results: AWT gt; 2.28mm was associated with decreased aortic cohesion (P7:131.7#xB1;66.3 vs.153.7#xB1;89.5 p=0.02; P8:2.95#xB1;1.55 vs.3.78#xB1;1,90 plt;0.01; P9:4.22#xB1;1.75 vs.4.94#xB1;2.12 plt;0.01) and increased media degeneration (45.8%vs.15.8% plt;0.01) compared to AWT #x2264; 2.28mm. Diameter of ascending aorta did not correlate with AWT (p=0.20). Majority of patients with AD presented with normal aortic diameter (13/18, 72.2%) and had an AWT gt; 2.28mm (15/18, 83.3%).